A concepção docente sobre avaliação da aprendizagem nos anos iniciais do ensino fundamental: novas experiências, velhas práticas? - Ferreira, Maria Angélica Martins (2022)
A – here defined as the act of measuring a study experience (in theory) a learning space – occupation in the school training process. However, in general, it is an examination rather than an assessment of understanding, incurring in misunderstanding, notably by teachers, but only (LUCKESI, 2002). As a result, they adopt a posture and resources that are at least questionable in relation to their evaluative practices, or that, in turn, affect both the representations about and the use of pedagogical social interventions based on them. In light of this, a scientific investigation was carried out with the aim of comparing conceptions about the act of evaluating, as well as its implications for teaching work in elementary school (initial years), in order to think about the relationship between evaluation and evaluation. learning. In addition, compare evaluated experiences or successful exits. This is a qualitative research, with a narrative design, having as target audience ten teachers working in the early years of elementary school (SAMPIERI; COLLADO; LUCIO, 2013). For data analysis, the technique of triangulation will be used, which consists of carrying out “a phenomenal and technical valuation of the primary data, in themselves and to the point of exhaustion”. Later, in a second analytical movement, the oral narratives are “contextualized, criticized, compared and triangulated” (GOMES et al., 2010, p. 185). The interpretive method takes place through three stages, namely: 1) preparation and gathering of data; 2) the quality assessment and, finally, 3) the elaboration of analysis categories. At first, we scrutinized the training paths, from schooling, through teacher professionalization, to continuing education or professional development, as indicated in the scientific literature, observing broader and more specific aspects regarding assessment. Following the path of analysis, one arrives at the conceptions regarding the organization of pedagogical work, including evaluative practices, analyzing, in turn, how they conceive and use evaluative resources, in an attempt to map eventual prosperous experiences, according to the notion of the surveyed teachers. In general, the results indicate practices that are still in the third generation of evaluation, however, they emerge in the direction of an evaluation for the fourth generation, whose evaluation is aligned to a constructivist perspective with actors involved with an evaluative practice negotiated in search of improvements in learning assessment. It is hoped that the results of the study can contribute with theoretical-methodological reflections on the theme, encouraging the expansion of the training margins of teachers, since they assume the role of triggering the training process.